Stadia the design and development guide - John, Geraint; Sheard, Rod; Vickery, Ben (Routledge, 2013)
"In this completely updated and redesigned edition of the essential and long-established Stadia, the authors offer their unrivalled expertise to all professionals who commission, plan, design, and manage high-quality sports venues.Ideas about the design and use of stadiums are evolving and this fifth edition includes the latest developments in the field. The chapters on sustainability and masterplanning have been completely updated and a new chapter on temporary sports buildings added. In addition, new case studies from recent projects around the world are included as the latest influential new buildings.In addition to a wide array of international information sources, the authors were able to draw on the experience of the design firm that delivered the 2010 Aviva stadium, Dublin, the 2004 Benfica stadium, Lisbon, the 2009 Soccer City FNB Stadium, Johannesburg and the 2011 Olympic Stadium, London. "--